TO STUDY EFFECT OF BOND STRENGTH WITH PROVIDED EFFECTIVE DEVELOPMENT LENGTH IN CONCRETE STRUCTURE - MR. AMAR PAWAR; PROF. AUTADE P.B (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The bond between concrete and reinforcement is very important to work as a composite behavior of Reinforced Concrete (RC). The several factors which influences the Bond stress in RC are embedment length, diameter of bar, cover, spacing of bars, transverse reinforcement, grade and confinement of concrete around the bars, type of aggregates used in concrete, type of bars and coating applied on bars, if any, for corrosion prevention. Adequate bonding between reinforcing bars and concrete is essential for the satisfactory performance of RC structures. The study primarily should focus to achieve best possible outcome for desired provision of development length in terms of strength and effect of development length on concrete structure for bond stress.